The Effect of the Implementation of the Inaportnet System on Ship Agency Services at PT Maritel Bahtera Abadi Balikpapan - Bayu Pambudy; Marihot Simanjuntak; Mauritz H. M Sibarani; Agus Leonard Togatorop; Jarot Delta Susanto (Meteor STIP Marunda, 2023)
This study examines the effect of the Inaportnet system on ship agency services at PT. Maritel Bahtera Abadi in Balikpapan. Inaportnet is Indonesia's integrated electronic port clearance platform, mandated by Ministry of Transportation Regulation No. 192/2015, designed to streamline vessel arrival and departure documentation. Using a quantitative approach with survey data from 51 respondents comprising shipping agents, port authority staff, and stevedoring company employees at KSOP Class I Balikpapan, the study employs Pearson correlation, simple linear regression, and coefficient of determination analysis through SPSS 25.0. The results show a moderate positive correlation (r = 0.472) between Inaportnet implementation and ship agency service quality, with the system explaining 53.4% of the variance in service quality (R² = 0.534). The t-test confirms the relationship is statistically significant (t = 3.750, p = 0.000 < 0.05). However, the study also documents operational challenges including 37 system error incidents across 179 vessel visits during the observation period, seven maintenance shutdowns, and persistent gaps between target and actual approval processing times. The findings suggest that while Inaportnet has a significant positive effect on agency services, system reliability issues and the continued requirement for face-to-face approval at KSOP Balikpapan limit its full potential.